Extranodal Rosai-Dorfman disease involving soft tissue associated with increased IgG4 plasma cells - Karen D. Thomas; Peggy Delahoussaye; Mary R. Schwartz; Alberto G. Ayala; Jae Y. Ro (Elsevier, 2021)
Background: Rosai-Dorfman disease (RDD) is a rare entity characterized by lymphadenopathy with dilated lymph node sinuses containing lymphocytes, plasma cells, and histiocytes exhibiting emperipolesis. IgG4-related disease (IgG4-RD) is relatively more common and is characterized by mass-forming lesions with dense lymphoplasmacytic infiltration, numerous IgG4 positive cells, fibrosis which is at least focally storiform, and obliterative phlebitis. Concomitant RDD and IgG4-RD is rare, and the significance of this association remains unclear. Case presentation: A 64-year-old female presented with the gradual onset of a painful right gluteal mass. The mass was clinically suspected to represent an infected sebaceous cyst and was surgically resected. Histological examination revealed a mixed inflammatory reaction in adipose tissue. There were areas of histiocytic proliferation with phagocytosis of inflammatory cells (emperipolesis), predominantly lymphocytes and plasma cells. There was also prominent storiform sclerosis with dense collections of plasma cells. No obliterative thrombophlebitis was seen. Immunohistochemical staining highlighted S100-positive cells with emperipolesis, greater than 50 IgG4 positive cells per high power field, and an IgG4/IgG ratio of greater than 40%. The histologic and immunohistochemical findings were those of RDD with concomitant IgG4-RD. Conclusions: There is limited literature on RDD with increased IgG4-positive plasma cells; and the exact relationship and clinical significance of this finding remains undetermined. We present here a case with combined RDD and IgG4-RD and review the relevant literature.